Financing for development challenges in Caribbean SIDS : a case for review of eligibility criteria for access to concessional financing - Bourne, Compton (UNDP Port-of-SpainTT, 2015)
Presents an analysis of the development challenges with a focus on recent trends and the current situation. Examines the financing challenges and provides statistical data on key trends in relation to domestic savings and investment capacity, fiscal capacity, government domestic and foreign debt, and analyses how these trends and patterns are affecting efforts to invest in sustainable development in the Caribbean. Discusses trends and patterns in official development assistance to the Caribbean. Looks at how access to development finance might be improved and makes specific recommendations.\n